DNA Flow cytometric analysis of the human testicular tissues to investigate the status of spermatogenesis in azoospermic patients - Arka Baksi (Nature Portfolio, 2018)
Abstract A single, rapid and reproducible diagnostic test to predict the type of azoospermia and outcome of sperm retrieval is not yet available. So the feasibility of employing DNA flow cytometry for rapid investigation of the status of spermatogenesis in the patients with azoospermia was investigated. Testicular biopsies of 44 patients with azoospermia undergoing sperm-retrieval surgery and 4 controls were analyzed by flow cytometry to ascertain their testicular germ-cell patterns. The observed germ-cell pattern was further confirmed by RT-PCR analysis of the cell-specific markers and histology for some patients. The patients with Obstructive Azoospermia (OA) exhibited normal spermatogenesis similar to the control fertile patients showing the presence of diploid, double-diploid and haploid cells. The non-obstructive azoospermia (NOA) patients exhibited disrupted spermatogenesis with arrest at the pre-meiotic (only diploid cells present) or meiotic (diploid and double-diploid cells present) stages. The germ-cell pattern, as ascertained by flow cytometry, provided a clear picture of the intra-testicular spermatogenesis and the presence of spermatozoa in the patients’ testes, which was prognostic of their sperm-retrieval. DNA flow cytometry test to ascertain the testicular germ-cell pattern is simple in execution, analysis and interpretation, requires small amount of tissue and provides quantitative data about the status of spermatogenesis in patients. This test would allow comparable analysis of the status of spermatogenesis in patients across clinics and may form the basis for deciding future treatment and intervention strategies.